About the interaction of positrons with hydrogen and helium atoms - Shalenov, Е.О.; Dzhumagulova, К.Н.; Tashkenbayev , Е.А.; Seitkozhanov , E.С.; Jumagulov, М.Н. (Recent Contributions to Physics, 2025)
The processes of elastic scattering of positrons on hydrogen and helium atoms based on the optical interaction potential were investigated. The problem was solved using the Calogero equation to determine phase shifts. The obtained phase shifts for s-, p-, and d-waves demonstrate characteristic patterns with increasing positron’s energy. A comparison of our results with previous studies confirmed their reliability. The variation of the differential scattering cross-section depending on the scattering angle and positron’s energy was also studied. The investigation of positron-atom interactions is crucial for understanding fundamental atomic processes and has implications in various fields, including antimatter research and medical imaging techniques. In this study, we applied the optical potential method to model the interaction between positrons and atomic targets, which provides a more accurate representation of the scattering dynamics. The numerical solution of the Calogero equation allowed us to compute phase shifts, which are essential in characterizing the scattering process. Our results revealed that phase shifts exhibit distinct trends for different angular momentum states, providing insight into the behavior of positron scattering at varying energy levels. The differential cross-section analysis further illustrated the angular dependence of scattering, highlighting key variations influenced by interaction potentials.